X-ray Diffraction Study of Organic Mixed Crystals - Patwari, S.B.; Baseer, M.A.; Vartale, S.P.; Patil, S.R. (Asian Journal of Chemistry, 2010)
Pyrene doped anthracene organoluminophors formed solid solutions. Pyrene in anthracene shows point defects and can be analyzed by X-ray studies. Study of these defects is very significant in solid state devices.